Stability of an ionization front in Bondi accretion - Keto, Eric; Kuiper, Rolf (Monthly notices of the Royal Astronomical Society, 2021)
Spherical Bondi accretion is used in astrophysics as an approximation to investigate many types of accretion processes. Two-phase accretion flows that transition from neutral to ionized have observational support in high-mass star formation, and have application to accretion flows around any ionizing source, but the hydrodynamic stability of two-phase Bondi accretion is not understood. With both semi-analytic and fully numerical methods, we find that these flows may be stable, conditionally stable, or unstable depending on the initial conditions. The transition from an R-type to a D-type ionization front plays a key role in conditionally stable and unstable flows.